Collective wondering: enabling productive uncertainty in agroecological codesign. Issue 1 (2nd January 2022) - Wernli, Markus
ABSTRACT: This paper explores the transformative relations of unknowable possibility in three urban communities which upcycle human waste. Working with communities – human and nonhuman – is approached by applying the dynamic model of collective wondering conceived as (i) provisional proposition, (ii) responsiveness to difference, and (iii) affirmation in/of uncertainty. The communities act in concert with people, microbes, and earthworms to address unsustainable food systems. Their profoundly self-implicating engagement on the material, social and cultural level stems from a pendulation between actionable immersion (wondering at) and perspectival detachment (wondering about). Community – understood as togetherness in wondering – becomes a conduit for imaginative, counter-intuitive thinking, and doing that can diversify existent, dominant, and hegemonic perspectives. Three agroecological cases illustrate how cultivating a rich, interactive context for exchanging or moving positions give birth to a plurality of perspectives, human and nonhuman, on the world. Since physical, social, and cultural positions in people and groups are never fully determined, codesign that provides ample possibility for repositioning – including unsettling bathroom routines, group debates, compost care, and agroecological tinkering – is crucial for opening perspectives and influencing how people act in close relation with unknowable otherness.